MENINGKATKAN KESADARAN HUKUM DALAM MEMBENTUK PERILAKU BIJAK BERMEDIA SOSIAL DI KALANGAN PELAJAR: SOSIALISASI DI MA DARUL IRFAN KOTA SERANG - Aldi Hidayat; Tiara Masayu Auliyadina; Riska Harmonis; Aulia Rahmawati; Dimas Febriansyah (Jurnal Riset Multidisiplin Edukasi, 2026)
This program aims to increase legal awareness and responsible social media behavior among students at MA Darul Irfan, Serang City. Through lectures, discussions, case studies, and simulations, students learned about legal rules, digital ethics, and the consequences of online behavior. Results showed improved understanding, more cautious attitudes, and more responsible social media use. The program highlights the importance of legal education and digital literacy for a safe and ethical online environment.